The Role of Giri Mulya Study Group Community in Improving Community Empowerment - Ali Yusuf; Heryanto Susilo; Sjafiatul Mardliyah; Rivo Nugroho (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2022)
This study examinedcommunity needs for community empowerment oriented to regional potential. The empowerment was conducted by Giri Mulya Study Group Community using the community-based community resource management process. This community is a form of a development strategy and community empowerment that contributes to controlling and managing productive resources. This research employed thequalitative research method, while the approach used in this research was the case study approach. The research informants were selected using the snowball sampling technique, and data were collected through observation and in-depth interviews. Giri Mulya Study Group Community development had a positive impact on community empowerment in Munggugebang village. Cooperation that existedamongelements of society can be a significant impetus to carry out an empowerment process. Sustainability of education in the Giri Mulya Study Group Community is the most basic effort in empowering an area, in this case, rural areas.